Akt2 and p‐Akt overexpression in oral cancer cells is due to a reduced rate of protein degradation. Issue 1 (22nd September 2015) - Archewa, Prakasit; Pata, Supansa; Chotjumlong, Pareena; Supanchart, Chayarop; Krisanaprakornkit, Suttichai; Iamaroon, Anak
Abstract: Objective: To quantitatively measure the increased expression of Akt2 and its phosphorylated form (p‐Akt) in oral cancer cell lines and investigate the post‐translational mechanism for Akt2 and p‐Akt overexpression. Methods: Three oral cancer cell lines and three cell lines of primary human oral keratinocytes (HOKs) were cultured and the degrees of Akt2 and p‐Akt expression was evaluated by immunoblot analysis and flow cytometry. Each cell line was incubated with cycloheximide, an inhibitor of new protein synthesis, for various times to quantitatively determine the remaining expression levels of Akt2 and p‐Akt by flow cytometry. The localization of Akt2 and p‐Akt was assessed by immunofluorescence. Results: The levels of Akt2 and p‐Akt proteins were significantly higher in cancer cell lines than those in HOKs ( P < 0.05). When the new protein synthesis was blocked by cycloheximide treatment, the degradation rate of Akt2 and p‐Akt in oral cancer cells was significantly lower than that in HOKs ( P < 0.05). Both Akt2 and p‐Akt were more intensely stained in the cytoplasm of cancer cells, whereas HOKs expressed Akt2 and p‐Akt only minimally. Conclusion: Both Akt2 and p‐Akt were overexpressed in oral cancer cells, which may be partly explained by a reduced rate of protein degradation in order to maintain high cytosolic levels.